2007
DOI: 10.1021/ma061547m
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Analysis of α-Olefin Enchainment in Poly(α-olefins) Produced with Nickel and Palladium α-Diimine Catalysts

Abstract: α-Diimine complexes of palladium and nickel catalyze the polymerization of α-olefins to give new materials that range from low-T g elastomers to low-melting, partially crystalline polymers. The 1H and 13C NMR spectra of the resulting polymers have been assigned in detail. Many unique microstructural features of the complex polymers have been identified. Mechanistic models that involve the 1,2- and 2,1-insertion of the α-olefins, chain walking, and insertion at certain points along the chain have been construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 40 publications
6
96
0
Order By: Relevance
“…In contrast, Pd-and Ni-diimine catalysts afford polyethylenes with highly branched structures and poly(a-olefin)s containing non-branched polymethylene repeating units, respectively (Scheme 2 (I)). 47,[52][53][54][55][56][57] The production of these polymers can be attributed to the occurrence of chain-walking reactions, in which alkylpalladium and alkylnickel species at the growing ends of the polymer undergo repetitive bhydrogen elimination of vinyl-terminated polyolefins followed by reinsertion of the coordinated olefin into the metal-hydrogen bond (Scheme 2 (II)).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Pd-and Ni-diimine catalysts afford polyethylenes with highly branched structures and poly(a-olefin)s containing non-branched polymethylene repeating units, respectively (Scheme 2 (I)). 47,[52][53][54][55][56][57] The production of these polymers can be attributed to the occurrence of chain-walking reactions, in which alkylpalladium and alkylnickel species at the growing ends of the polymer undergo repetitive bhydrogen elimination of vinyl-terminated polyolefins followed by reinsertion of the coordinated olefin into the metal-hydrogen bond (Scheme 2 (II)).…”
Section: Introductionmentioning
confidence: 99%
“…1). Finally, apolar olefins (e.g., α-olefins) commonly afford mixtures of both insertion modes in palladium-catalyzed Mizoroki-Heck (15) and polymerization reactions (16), whereas closely related nickel-catalyzed polymerizations of α-olefins can proceed with high selectivity by 1,2-insertion (17)-e.g., under kinetically controlled low-temperature conditions when sterically demanding ligands coordinate to nickel (16,18).The accepted rationale for these reactivity patterns is that electronic effects govern the regiochemistry of insertion for polarized carbon-carbon double bond substrates: In the Cossée-Arlman-type insertion step, the metal-bound, nucleophilic carbon atom migrates to the lower electron-density carbon atom of the double bond, while the electrophilic palladium atom migrates to the higher electron-density carbon atom of the double bond. In contrast, the insertion regiochemistry of apolar carbon-carbon double bonds is rather determined by steric effects (given that there is little electronic discrimination of the two olefinic carbon atoms), and under strict kinetic control the 1,2-insertion mode may prevail.…”
mentioning
confidence: 99%
“…1). Finally, apolar olefins (e.g., α-olefins) commonly afford mixtures of both insertion modes in palladium-catalyzed Mizoroki-Heck (15) and polymerization reactions (16), whereas closely related nickel-catalyzed polymerizations of α-olefins can proceed with high selectivity by 1,2-insertion (17)-e.g., under kinetically controlled low-temperature conditions when sterically demanding ligands coordinate to nickel (16,18).…”
mentioning
confidence: 99%
“…[19] The 1 H NMR spectrum of the polymer obtained showed a signal at d = 2.36 ppm, assigned to the CH 2 of the cyclopentane ring, as well as a peak at d = 1.99 ppm, assigned to the CH 2 and CH carbon atoms of the cyclopentane ring at an intensity ratio of 2:4, which indicates the incorporation of the barbiturate unit of 4 a-III into the polymer end. The relative-intensity ratio of the signal at d = 2.36 ppm to the signals of the hydrogen atoms of the 1-hexene unit (d = 1.5-0.65 ppm) is 1:801, which corresponds to M n = 11 000.…”
Section: Synthesis and Gelation Of Telechelic Polya C H T U N G T R Ementioning
confidence: 86%
“…Mechanistic studies of the polymerization of a-olefins revealed that insertion of a vinyl group into the Pd À CH 2 bond occurs more easily than insertion into the Pd À CH bond. [4,19] Room temperature 13 C NMR spectroscopy of the polymerization reaction of I catalyzed by 1 a/NaBARF revealed the presence of signals due to the carbonyl carbon atom attached to Pd (d = 187.5 ppm). The polymer end maintains coordination of the carbonyl group to Pd in the resting state, indicated by the similarity of the peak position to isolated and fully characterized 4 a-I and 4 a-IV (d = 187.6 and 187.9 ppm, respectively).…”
Section: A-iv)mentioning
confidence: 99%